Evaluasi Manajemen Pembelajaran Biologi Kelas X - Eni Suyantri; Baiq Sri Handayani; Tri Ayu Lestari (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Biology learning management is very important in an effective and efficient biology teaching and learning process. With biology learning management, the teacher plans, organizes, leads, and evaluates learning materials. This study aims to identify the strengths and weaknesses in biology learning management for class X at SMA Negeri 3 Mataram and provide insights for further improvement and development. This type of research is descriptive evaluative research with a quantitative approach. Based on the evaluation results, it was found that the good category for each stage of biology learning management was 81% starting from the planning stage, 75% organizing, 80% leadership, and 83% evaluation. Some of the obstacles encountered by teachers in biology learning management at SMA Negeri 3 Mataram were that teachers had difficulty planning/determining methods and models to be used in the learning process, teachers were not assertive in directing students to form groups, and teachers were unable to maintain student focus due to the organization of learning resources right.